(untitled) (Experimental biology, 2015)
F2 generation plants of Kazakhstanskaya-10 variety, regenerated from tissue culture of immature embryos, served as material of the study.To detect changes on studied guantitative traits statistical parameters were used. Analysis of gliadin (wheat storage protein) electrophoretic spectrum was carried out. It has been shown, that gliadin spectrum was identical for regenerants and donor plants.